Growth Mindset Profiles of Elementary School Teachers with Inclusive Students: An Analysis by Professional Status, Age, and Gender - Ni Luh Sri Wida Wati; Putu Nanci Riastini; Basilius Redan Werang (Universitas Pendidikan Ganesha, 2025)
Many inclusive elementary school teachers still have a fixed mindset, which can hinder the development of students with special needs. This mindset results in low expectations of students’ abilities and the implementation of less flexible teaching methods. Teachers with a growth mindset are more capable of creating a supportive learning environment that fosters students' potential. This study aims to identify the growth mindset profile of elementary school teachers based on professional status, age, and gender. A descriptive quantitative method was used, involving 51 teachers as respondents. Data were collected using a Likert-scale questionnaire adapted from Carol Dweck’s Mindset Quiz and analysed using descriptive statistics. Results showed that 72.55% of teachers had a growth mindset with some fixed ideas, 17.65% had a strong growth mindset, and 9.80% exhibited a fixed mindset. Certified teachers and those aged 36–45 tended to have a stronger growth mindset, while younger teachers were more likely to have a fixed mindset. This study highlights the need for training and mentoring programs to strengthen teachers’ growth mindsets in supporting more effective inclusive education.